A membrane-based green and low-cost system for ensuring safe drinking water in a selenium-affected region. (15th December 2022) - Malhotra, M.; Roy, M.; Pal, P.
Abstract: Towards an efficient, low-cost solution to the problem of contamination of groundwater by selenium leached out from earth's mineral crust, a new system is developed using a novel graphene-based nanocomposite membrane. The system not only purified selenium-contaminated groundwater with high degree but also ensured safe disposal of the rejected selenium through algorithmic chemical stabilization in a mineral matrix. All experiments were conducted with live contaminated water from selenium affected area rather than using synthetic solution in a semi-pilot unit involving a largely fouling-free flat sheet cross-flow membrane module. Pure water flux of up to 190 Lm −2 h −1 (LMH) with 96–97% selenium rejection at an optimum operating pressure of only 14 bar could be achieved. Rejected selenium was stabilized in mineral matrix through chemical coagulation-precipitation using suitable coagulants following prior optimization of the critical operating parameters by Model-based calibration toolbox (MATLAB R2020a). A high degree of stabilization efficiency (99.8%) could be achieved as reflected in an error-index of only 1.13%. For selenium-affected region, the membrane-integrated hybrid treatment system proved to be a potential candidate technology offering safe drinking water at an approximate cost of only 1.77 /m 3 which was found to be affordable to the consumers in subsequent willingness to pay survey. Graphical abstract: Image 1 Highlights (JEM): Membrane-based novel water treatment system developed for selenium removal. Module with tailor-made GO-Fe III (OH)x nanocomposite removed 97% Se. Non-conventional module ensured sustained high flux of 190LMH at only 14 bar. Willingness to pay coupled with techno-economic analysis proved acceptability.